RAPID ASSESSMENT OF AGGREGATION ABILITIES AND SURFACE PROPERTIES OF PLATELETS AND RED BLOOD CELLS - ILYA NIKOLAEVICH MEDVEDEV,; VLADIMIR ILICH MAKSIMOV,; ANDREY VLADIMIROVICH PARAKHNEVICH,; SVETLANA YURYEVNA ZAVALISHINA,; NADEZHDA VIKTOROVNA KUTAFINA, (International Journal of Pharma and Bio Sciences, 2016)
Rheological properties of erythrocytes and platelets define blood rheology in general. The role of their aggregation and surface geometry is highly essential. The screening remains in demand in practical biology. Erythrocyte aggregation activity can be recorded quite quickly and easily with an optical microscope by counting in a hemocytometer of rouleaux, aggregated and non-aggregated erythrocytes in a washed erythrocyte suspension in blood. Erythrocyte cytoarchitectonics can be determined with a light phase contrast microscope. Assessment of erythrocyte microrheological properties should be added with platelet aggregation evaluation, which can be carried out visually by a simplified method. The percentage of active forms of platelets and aggregates in blood can be assessed with a phase contrast microscope. No expensive equipment is required to assess the main microrheological properties of erythrocytes and platelets for all details of their dynamics at multiple testing. These morphofunctional methods help determine that in norm a changed form is noted in blood only in an insignificant number of red blood cells and platelets. Under pathology, these indicators can be substantially changed due to altered rheological properties of red blood cells and platelets, significantly impairing the microcirculation.